P3_8 Elysium: How Fast Did the Atmosphere Escape? - Buttery, H. W.; Middleton, C. J.; Moore, C. D.Y.; Peck, R. H. (Physics Special Topics, 2016)
In this paper, the rates at which the atmosphere of the roofless Elysium space-station would escape for var- ious atmospheric angular velocities were considered. The resulting relative mass flow rates were calculated to be between 3.6 × 10−5 - 2.4 × 10−4 M/s. From these, the times over which the entire atmospheric mass, M, would be replenished ranged between 1.2 - 7.8 hours, leading to an impractical space-station.